Myosin phosphatase isoforms and related transcripts in the pig coronary circulation and effects of exercise and chronic occlusion - Zheng, Xiaoxu (2014)
Myosin phosphatase (MP) is a key target of signaling pathways that regulate smooth muscle tone and blood flow. Alternative splicing of MP targeting subunit (MYPT1) exon 24 (E24) generates isoforms with variable presence of a C-terminal leucine zipper (LZ) required for activation of MP by NO/cGMP. Here we examined the expression of MP and associated genes in a disease model in the coronary circulation. Female Yucatan miniature swine remained sedentary or were exercise-trained beginning eight weeks after placement of an ameroid constrictor around the left circumflex (LCX) artery. Fourteen weeks later epicardial arteries (~1 mm) and resistance arterioles (~125 µm) were harvested and assayed for gene expression. MYPT1 isoforms were distinct in the epicardial arteries (E24−/LZ+) and resistance arterioles (E24+/LZ−) and unchanged by exercise training or coronary occlusion. MYPT1, CPI-17 and PDE5 mRNA levels were not different between arteries and arterioles while Kir2.1 and eNOS were 6.6-fold and 3.9-fold higher in the arterioles. There were no significant changes in transcript abundance in epicardial arteries of the collateralized (LCX) vs. non-occluded left anterior descending (LAD) territories, or in exercise-trained vs. sedentary pigs. There was a significant 1.2 fold increase in CPI-17 in collateral-dependent arterioles, independent of exercise, and a significant 1.7 fold increase in PDE5 in arterioles from exercise-trained pigs, independent of occlusion. We conclude that differences in MYPT1 E24 (LZ) isoforms, eNOS, and Kir2.1 distinguish epicardial arteries and resistance coronary arterioles. Up-regulation of coronary arteriolar PDE5 by exercise and CPI-17 by chronic occlusion could contribute to altered vasomotor responses and requires further study.